2012
DOI: 10.1016/j.freeradbiomed.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione redox cycle dysregulation in Huntington’s disease knock-in striatal cells

Abstract: a b s t r a c tHuntington's disease (HD) is a CAG repeat disorder affecting the HD gene, which encodes for huntingtin (Htt) and is characterized by prominent cell death in the striatum. Oxidative stress was previously implicated in HD neurodegeneration, but the role of the major endogenous antioxidant system, the glutathione redox cycle, has been less studied following expression of full-length mutant Htt (FL-mHtt). Thus, in this work we analyzed the glutathione system in striatal cells derived from HD knock-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 45 publications
4
51
0
Order By: Relevance
“…4A,B). A rise in glutathione levels in mutant cells, despite decreased GCL activity, was previously demonstrated [17]. Therefore, we tested whether insulin or IGF-1 could alter GSH and GSSG levels.…”
Section: Full-length Mhtt Modifies Sod1/2 Gcl Catalytic and Glutathimentioning
confidence: 79%
See 4 more Smart Citations
“…4A,B). A rise in glutathione levels in mutant cells, despite decreased GCL activity, was previously demonstrated [17]. Therefore, we tested whether insulin or IGF-1 could alter GSH and GSSG levels.…”
Section: Full-length Mhtt Modifies Sod1/2 Gcl Catalytic and Glutathimentioning
confidence: 79%
“…Reduced activity of SOD1 was also observed in cortex and cerebellum of post-mortem human brain tissues [7] and in erythrocytes [5] of HD patients. In a previous study we demonstrated increased ROS levels and decreased GCL activity, despite increased glutathione levels in HD striatal cells, which occurred as a result of a lower capacity of multidrug resistance-associated protein 1 (Mrp1) to export GSH to the extracellular space [17].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations